A review on the relationship between the distal 1q21.1 microdeletion and schizophrenia - Xinpeng Guo; Xinpeng Guo; Xinpeng Guo; Junrong Guo; Junrong Guo; Xijing Liu; Xijing Liu; Ting Hu; Ting Hu (Frontiers in Genetics)
Schizophrenia is a complex neuropsychiatric disorder closely associated with genetic factors. Copy number variations (CNVs) play a key role in the genetic etiology of schizophrenia, with the distal 1q21.1 microdeletion identified as a rare CNV that serves as a significant genetic risk factor for the disorder. This microdeletion is found in 0.2%–0.6% of individuals with schizophrenia and is associated with an eightfold increased risk of developing the condition. The distal 1q21.1 region contains several schizophrenia risk genes, including PRKAB2, BCL9, CHD1L, GJA5, and GJA8. This review focuses on the roles of these five genes in brain function and explores their potential pathophysiological mechanisms in schizophrenia. By synthesizing current evidence, this review aims to deepen the understanding of schizophrenia by outlining its genetic architecture and molecular mechanisms, thereby providing a comprehensive framework for exploring disease pathogenesis.